Nypa Frutican Rachis as building envelope heat insulator - Kesot, Mohd Jahaya; Hanafi, Dirman; Shamsuddin, Abu Ubaidah; Ahmad, Ida Laila (Penerbit UTHM, 2020)
This research is conducted to investigate the possibility of cellulose in Nypa Frutican Rachis to achieve thermal comfort. As Malaysia was known as tropical country which has hot and humid climate, this research focus on to study the transfer of heat through Nypa Frutican Rachis as a roof. Since only Nypa leaves have been used as a roof and have been applied until now in East Malaysia, this project uses an innovation of Nypa palm by using its rachis that contain chemical material that have lower thermal conductivity value such as cellulose and lignin as a roof or building envelope heat insulator. This paper described the experimental study method by measuring the temperature of outer and inner surface of Nypa Frutican Rachis on small physical model study. The temperature was measured by using Digital Infrared Thermometer. The average outer and inner tempe rature for five consecutive days was obtained from the experiment is highlighted. Results show that the average of heat loss and heat transfer conduction for five consecutive days are 9.63 W/h and 9.86 W. This experiment shows a good result and proved that Nypa Frutican Rachis is suitable and effective to be a building envelope heat insulator.